Fluoride Removal Using Alumina Nanoparticles - Lopog, Ecrolien Liberty (Universiti Sains Malaysia, 2006)
The presence of fluoride in drinking water, in quantities in excess of permissible limits is a serious matter of concern from a public health point of view. High concentration of fluoride can lead to fluorosis. Various adsorbents for removing fluoride from drinking water have been studied in the past. In this research, alumina nanoparticles was proposed for the removal of fluoride from drinking water. Batch experiments were conducted to determine the efficacy of alumina nanoparticles in fluoride removal from water. The fluoride removal performance was investigated as a function of pH, contact time, initial fluoride concentration and adsorbent dosage. The dependence of the adsorption of fluoride on the pH of the solution has been studied to achieve the optimum pH value. It was found that the maximum adsorption takes place at pH 2.5. Contact time analysis revealed that the percent fluoride removal increases initially as contact time increases, but then it gradually approaches a more or less constant value, indicating that the equilibrium has been attained. The experiments showed that 120 minutes was the suitable contact time. In kinetic study, the Second Order Integral model was found to express the sorption kinetics of fluoride better. Study on the influence of adsorbent dosage showed that the efficiency of the fluoride removal increases with the increase of adsorbent dosage. The removal efficiency for 2, 4, 6, 8, and 10 g/l of alumina nanoparticles is 15, 24.80, 33.87, 41.33, and 48.53 % respectively. Adsorption isotherms have been modeled by Langmuir and Freundlich equations and isotherm constants for both isotherms were calculated. In isotherms studies, both models were found to be suitable to describe the adsorption of fluoride onto the alumina nanoparticles. The capacity of alumina nanoparticles is 4.4033 mg/g which can be obtained from the Langmuir isotherm.